Investing in the digital age: Exploring the underlying motivations of P2P lenders - Putri, Elvita Rahmayanti; Tandiono, Rosaline (Edelweiss Applied Science and Technology, 2025)
This study investigates the underlying motivations of lenders in Peer-to-Peer (P2P) lending, using the Theory of Planned Behavior as its framework. Based on qualitative interviews, findings reveal that lenders exhibit a positive attitude toward P2P lending, driven by opportunistic investment decisions, the perception of relatively low-risk investments, and the availability of disposable income. This attitude is further reinforced by the accessibility of investment-related information on digital platforms. Beyond individual motivations, social influence plays a crucial role, as family members and digital influencers significantly impact lenders' investment choices. Additionally, perceived behavioral control in digital investment environments is shaped not only by regulatory structures and platform transparency but also by decentralized information sources, investment flexibility, and experiential learning. These findings emphasize the transformative role of digital finance in shaping investor autonomy and risk perception. The study offers practical insights for P2P lending platforms to develop more effective communication and engagement strategies tailored to digitally savvy investors.